Tabu e preconceito linguístico - Orsi, Vivian [UNESP] (My University, 2011)
The lexicon of a language shows the way the community views the world, in its different aspects. Hence, through the study of the lexicon we can get a clearer idea of the different forms of prejudice present in a society. The aim of this study is to present reflections and theories concerning obscene lexical items and linguistics taboos associated to them, and to discuss the linguistic prejudice that this kind of lexicon may suffer.

O léxico de uma língua permite que nele se entreveja o modo como a comunidade vê o mundo que a circunda, em seus diferentes aspectos. Assim, por meio do seu estudo podemos ter uma ideia dos preconceitos que permeiam a sociedade. O objetivo deste trabalho é apresentar reflexões e teorizações referentes aos itens léxicos obscenos e aos tabus linguísticos a eles subjacentes e abordar o preconceito linguístico.
Keywords: Lexicologia; Léxico Erótico-Obsceno; Tabu; Preconceito linguístico; Lexicology; Obscene lexicon; Taboo; Linguistic prejudice